6x-12y-36=0

Move all terms not containing y to the right side of the equation.

Subtract 6x from both sides of the equation.

-12y-36=-6x

Add 36 to both sides of the equation.

-12y=-6x+36

-12y=-6x+36

Divide each term by -12 and simplify.

Divide each term in -12y=-6x+36 by -12.

-12y-12=-6x-12+36-12

Cancel the common factor of -12.

Cancel the common factor.

-12y-12=-6x-12+36-12

Divide y by 1.

y=-6x-12+36-12

y=-6x-12+36-12

Simplify each term.

Cancel the common factor of -6 and -12.

Factor -6 out of -6x.

y=-6(x)-12+36-12

Cancel the common factors.

Factor -6 out of -12.

y=-6(x)-6(2)+36-12

Cancel the common factor.

y=-6x-6⋅2+36-12

Rewrite the expression.

y=x2+36-12

y=x2+36-12

y=x2+36-12

Divide 36 by -12.

y=x2-3

y=x2-3

y=x2-3

y=x2-3

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Find the values of m and b using the form y=mx+b.

m=12

b=-3

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: 12

y-intercept: -3

Slope: 12

y-intercept: -3

Choose 2 to substitute in for x to find the ordered pair.

Replace the variable x with 2 in the expression.

f(2)=22-3

Simplify the result.

Divide 2 by 2.

f(2)=1-3

Subtract 3 from 1.

f(2)=-2

The final answer is -2.

-2

-2

The y value at x=2 is -2.

y=-2

y=-2

Choose 0 to substitute in for x to find the ordered pair.

Replace the variable x with 0 in the expression.

f(0)=02-3

Simplify the result.

Divide 0 by 2.

f(0)=0-3

Subtract 3 from 0.

f(0)=-3

The final answer is -3.

-3

-3

The y value at x=0 is -3.

y=-3

y=-3

Create a table of the x and y values.

xy0-32-2

xy0-32-2

Graph the line using the slope and the y-intercept, or the points.

Slope: 12

y-intercept: -3

xy0-32-2

Graph 6x-12y-36=0